Customer Relationship Management and IT - Dintsis, Danil (IntechOpen, 2020)
All of us enjoy individually specific service or a product that is delivered for us only. Customer relationship management (CRM) is the area of expertise that helps companies to work with customers based on their specific needs or requirements. To reach success CRM systems implement the most powerful math and IT tools such as statistical analysis, artificial neural nets, and graph systems. This book deals with the practical implementation and meta-analysis of CRM experience in various locations and business areas. The authors have produced a great book and provided meta-analysis of the latest CRM systems and a roadmap of their development. In the chapters, our readers will find descriptive analysis of CRM models, applied tools, and methods.